Impact Assessment of Bidi Tobacco in Gujarat - Srinivas, A.; Reddy, D. Damodar; Reddy, K. Vishwanath; Baliwada, Hema; Krishna, S. Kasturi (Indian Journal of Extension Education, 2022)
Tobacco, the golden leaf is one of the important high value commercial crops grown in over 15 states in India. It is a highly remunerative crop fetching more economic benefits to the farmers. Among different types of tobacco, bidi tobacco is an important non-FCV tobacco grown largely in Gujarat. The present study was conducted in the year 2019 with an objective to assess the impact of tobacco crop on socio-economic transformation of tobacco farmers in Gujarat state. The total sample size of the study was 160. The average net returns from bidi tobacco were Rs. 65000/ha. in Gujarat compared to wheat (Rs. 25,000/ ha) and jowar (Rs. 15000/ha). The socio-economic impact was high for tobacco growers in terms of land size, annual income, expenditure pattern, possession of assets, net returns, habitat &educational security and social empowerment than non-tobacco farmers. The major constraints identified from tobacco farmers wereprice fluctuation, non-availability of labour, suckers problem and storage facilities. The different factors for growing tobacco were high profit, availability of timely and sufficient credit, location suitability and timely availability of inputs. For non-tobacco crops, the major factors for cultivation were location suitability, adoption of improved technology, quick payment to the produce and government support.
Keywords: Bidi tobacco; Constraints; Economic impact; Farmers; Jowar; Wheat